JOB INSECURITY DITINJAU DARI MOTIVASI KERJA PADA PEGAWAI PERJANJIAN KERJA WAKTU TERTENTU - Dwi Hurriyati; Apriyanti Apriyanti (Jurnal Ilmiah Psyche, 2022)
The application of the contract employee system so far has had several problems, one of which is due to the employment relationship which is always in the form of non-permanent or contractual ones. Make workers feel insecure because of status uncertainty that can interfere with work motivation. Researchers are interested in conducting research to find out the relationship between job insecurity and work motivation in employees with work agreements for a certain time in a city of Palembang. The research sample used a purposive random sampling technique with a total sample of 111 people. Data collection uses a job insecurity scale and a motivation scale. Data processing techniques using simple regretion analysis techniques. The results of the analysis of the research data show that the general correlation coefficient is r = 0.748 with an R square = 0.560 and p = 0.000 where p≤ 0.01. This shows that the hypothesis is accepted. The results of the study state that there is a very significant relationship between job insecurity and work motivation in employees with work agreements for a certain time